Swedish consumers´ views of cheese brands : an explorative survey among students’ views - Lindén, Charlotte; Åkesson, Elisabeth (SLU/Dept. of Economics, 2015)
Research shows that the Swedish consumption of cheese is increasing every year. The production of cheese in Sweden can not meet this increasing demand which leads to an increase in imported cheese. At the same time this sector within the food production is losing market shares rapidly. Today 50% of every consumed cheese in Sweden is produced abroad. This means that the Swedish industry has failed to meet the consumer’s need and missed the opportunity of an increasing national market and access to the export market. The import of cheese is strongly affecting traditional Swedish cheeses such as Grevé, Svecia, Herrgård and Präst, when consumers may have a decreasing knowledge of Swedish cheeses. Some trends may characterize and develop the Swedish cheese market. Due to consumers’ awareness and loyalty to brands, the brand constitute is a valuable asset. However, consumers pay different attention to special types of brand. Retailers’ private brands tend to be more important, since the loyalty towards retailers is increasing. Another trend is the increased import, when the market becomes more globalized. The aim of this thesis is to explore the views that Swedish consumers have of brands of yellow cheeses with a variety of attributes. The thesis concerns only the consumers’ perceptions of cheese and not their choise of cheese. A web-based survey was used to conduct the study. An e-mail questionnaire was sent out to a target group consisting of the students at the Swedish University of Agricultural Sciences. Total number of students was 4,618 and the response rate was 19%. The result shows that consumer perception of cheeses and various brands highlights the qualitative aspects as the most important. If a consumer perceives a cheese or a brand positively they will also perceive the same as of quality. It also indicates that there are a number of other attributes that are critical such as price, usability, taste and brand. It shows that a brand has a more positive association if the brand is associated with multiple attributes. Also some consumers consider themselves to be loyal when it comes to different brands and cheeses, they often return to the same brand and cheese when shopping. If a consumer is aware of a brand or a specific cheese, it is more likely to perceive that it is of quality also. This also applies if the consumer is sympathetic to the cheese or brand. The more attributes a cheese or a brand has, the more quality the consumer believes that it has and they will then have a positive perception towards the same.